2016
DOI: 10.1080/14767058.2016.1188379
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal counseling on exclusive breastfeeding using video – experience from a tertiary care teaching hospital, south India

Abstract: The video based health education program when combined with routine lactation counseling improved the knowledge regarding exclusive breastfeeding among postnatal primiparous mothers better than with routine lactation counseling alone. However, both interventions had similar effect on exclusive breastfeeding rate at six months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…21 Our survey data show that mothers' use of evidence-based newborn care practices at 4 weeks post delivery is relatively low, with the exception of exclusive breast feeding. The high rate of exclusive breast feeding (77%) is consistent with other studies from India at 4 weeks post delivery [21][22][23] as well as the India National Family Health Survey 2015-2016 rate of exclusive breast feeding for babies under 2 months old, 24 and aligns with our study team's expectations given the country's investments in breastfeeding promotion programmes. The rate of proper umbilical cord care (46%) is consistent with a systematic review of cord care practices in LMICs that found widespread traditions of applying substances to the umbilical cord, 25 and aligns with the study team's experience that clean/ dry cord care is not always discussed in hospital discharge instructions.…”
Section: Implications For Postnatal Education Programmingsupporting
confidence: 90%
“…21 Our survey data show that mothers' use of evidence-based newborn care practices at 4 weeks post delivery is relatively low, with the exception of exclusive breast feeding. The high rate of exclusive breast feeding (77%) is consistent with other studies from India at 4 weeks post delivery [21][22][23] as well as the India National Family Health Survey 2015-2016 rate of exclusive breast feeding for babies under 2 months old, 24 and aligns with our study team's expectations given the country's investments in breastfeeding promotion programmes. The rate of proper umbilical cord care (46%) is consistent with a systematic review of cord care practices in LMICs that found widespread traditions of applying substances to the umbilical cord, 25 and aligns with the study team's experience that clean/ dry cord care is not always discussed in hospital discharge instructions.…”
Section: Implications For Postnatal Education Programmingsupporting
confidence: 90%
“…The intervention translated into a better quality of care (Okawa et al, 2019 ). Higher rates of EBF were due to higher confidence levels and good dietary practices adopted post-intervention (Okawa et al, 2019 ).Strengthening efforts to enhance mothers’ self-confidence is essential in encouraging EBF, especially in countries with low EBF rates (Adhisivam et al, 2017 ; Chandhiok et al, 2015 ; Haroon et al, 2013 ; Opadeyi et al 2019 ; Victora et al, 2016 ; Tsegaye et al, 2019 ). The present study established that the best breastfeeding practices with long term benefits can be achieved by reinforcing education on ENC soon after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal counseling and support of mothers on breastfeeding techniques like positioning, attachment of baby and common breastfeeding difficulties and their solutions, expression of breast milk, builds confidence among mothers, and encouraging them to breastfeed their babies in a better way and job aids can improve counseling skills of nursing staff. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%